Histopathological Pattern of Abnormal Uterine Bleeding in Endometrial Biopsies - Mirza, Talat; Akram, Saadia; Mirza, Aamir; Aziz, Sadiya; Mirza, Tariq; Mustansar, Tazeen (Journal of Basic & Applied Sciences, 2012)
The study was conducted to determine the histopathological interpretation of endometrial curetting in relation to the very important and common problem of abnormal uterine bleeding. 1000 endometrial samples received at Ehsanullah Laboratories from January 2003 to December 2010 for the complaints of abnormal uterine bleeding were included in the study; these samples were received from Abbasi Shaheed Hospital and Civil Hospital Karachi along with pertinent clinical information. Out of 1000 endometrial samples presenting with abnormal uterine bleeding, major bulk 570 (57%) of cases revealed no organic pathology and a smaller group of cases 430 (43%) showed definitive endometrial pathology. Maximum numbers of cases were in perimenopausal age group (45-60 year). In majority of patients with no organic pathology, normal physiological phases of proliferation, secretory, menstrual and atrophic in old age were most commonly recorded. The most commonly seen organic lesions in this series were endometrial hyperplasia accounting for 130 cases (30%), chronic endometritis in 57 cases (13%) and endometrial polyps in 53 cases (12%). Histopathological evaluation of endometrial samples is helpful in determining the cause of abnormal uterine bleeding, especially indicated in over 35year age group to rule out malignancy and preneoplasia